The targets of regional models for state national policy - Popkov, Yuri V.; Tyugashev, Evgenii A. (The New Research of Tuva, 2013)
Discussing the problem of defining the targets of state national policy and in accordance with selected targets, authors offer a typology of regional models for state national policy in the Russian Federation.